The Implementation of Revenue Recognition According to PSAK No. 34 (Revised 2014) on Construction Company CV. M - Soraya, Meidina Siti (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
This research was conducted on CV. M is one of the construction companie located in Pontianak. The purpose of this research is to know the method of revenue and expense recognition applied by company based on PSAK No. 34 Revision 2014 (Contract of Construction). The analysis includes the calculation, the frsamework of financial statement presentation and the factors that affect the nonconformity. The method used in this research is qualitative method. Data supporting the research consist of pimary and secondary data.In this research, the writer cannot conclude whether CV. M has or not been in accordance with PSAK No. 34 (Revised 2014). Therefore, the authors provide an explanation of the factors and obstacles in this study. Factors such as data that support this research are not complete so there are some obstacles to research CV. M